Design of optimal fuzzy logic-PID controller using bee colony optimization for frequency control in an isolated wind-diesel system - Chaiyatham, T.; Ngamroo, I.; Pothiya, S.; Vachirasricirikul, S. (My University, 2009)
Generally, the inevitable problems in the fuzzy logic-PID (FLPID) control design are the trial and error of the setting of scale factors, membership functions and control rules. To solve these problems, this paper proposes the optimal FLPID controller design using bee colony optimization (BCO) for the load frequency control in the microglia system. The considered microgrid is the hybrid wind-diesel isolated system. The BCO is applied to automatically optimize the FLPID controllers of governor in the diesel side and blade pitch control in the wind side. Simulation studies show the superior robustness of the optimal FLPID against system parameters variation in comparison with the optimal PID controller and the non-optimal FLPID controller.
Keywords: Bee colony optimization; Frequency control; Fuzzy logic-PID controller; Isolated winddiesel generation system; Microgrid system